Online Learning: Student's Perception off Lecturer's Competence and its Influence on Achievement Motivation - Kusuma, Jaka Wijaya; Hamidah, Hamidah (International Journal for Educational and Vocational Studies, 2021)
In the midst of the current pandemic, online learning is the main choice in the world of education. However, there was a wide range of student responses to the learning process. Furthermore, it is known that the perception of students towards learning submitted by influential lecturers to generate interest in learning students in understanding the materials provided. Therefore, the purpose of this study is to obtain concrete information about: 1) how students perceive the competence of lecturers in applying online learning; 2) how to motivate students to excel during online learning; and 3) is there any influence of student perception on the competence of lecturers with the motivation of student achievement. This research uses a combination research design and its data collection method, namely survey by providing questionnaire questionnaire link with googleform. The subjects of the study were 274 students of the even semester of the academic year 2019/2020 at Bina Bangsa University who responded to the poll. The conclusion is that the perception of students is very diverse towards the competence of lecturers in applying online learning, as well as the motivation of student achievement. Although the percentage of incline is positive, not a few have responded negatively. Furthermore, it is known that there is a significant and moderate influence between the perception of students towards the competence of lecturers and the motivation of student achievement. In other words, if the student's perception of lecturer's competence increases, it will be accompanied by increased motivation for student achievement.